Hypertrophic cardiomyopathy is characterized by alterations of the mitochondrial calcium uniporter complex proteins: insights from patients with aortic valve stenosis versus hypertrophic obstructive cardiomyopathy - Paar, Vera; Haslinger, Michael; Krombholz-Reindl, Philipp; Pittner, Stefan; Neuner, Matthias; Jirak, Peter; Kolbitsch, Tobias; Minnich, Bernd; Schrödl, Falk; Kaser-Eichberger, Alexandra; Kopp, Kristen; Koller, Andreas; et al. (Frontiers in Pharmacology, 2023)
Introduction: Hypertrophies of the cardiac septum are caused either by aortic valve stenosis (AVS) or by congenital hypertrophic obstructive cardiomyopathy (HOCM). As they induce cardiac remodeling, these cardiac pathologies may promote an arrhythmogenic substrate with associated malignant ventricular arrhythmias and may lead to heart failure. While altered calcium (Ca2+) handling seems to be a key player in the pathogenesis, the role of mitochondrial calcium handling was not investigated in these patients to date. Methods: To investigate this issue, cardiac septal samples were collected from patients undergoing myectomy during cardiac surgery for excessive septal hypertrophy and/or aortic valve replacement, caused by AVS and HOCM. Septal specimens were matched with cardiac tissue obtained from post-mortem controls without cardiac diseases (Ctrl). Results and discussion: Patient characteristics and most of the echocardiographic parameters did not differ between AVS and HOCM. Most notably, the interventricular septum thickness, diastolic (IVSd), was the greatest in HOCM patients. Histological and molecular analyses showed a trend towards higher fibrotic burden in both pathologies, when compared to Ctrl. Most notably, the mitochondrial Ca2+ uniporter (MCU) complex associated proteins were altered in both pathologies of left ventricular hypertrophy (LVH). On the one hand, the expression pattern of the MCU complex subunits MCU and MICU1 were shown to be markedly increased, especially in AVS. On the other hand, PRMT-1, UCP-2, and UCP-3 declined with hypertrophy. These conditions were associated with an increase in the expression patterns of the Ca2+ uptaking ion channel SERCA2a in AVS (p = 0.0013), though not in HOCM, compared to healthy tissue. Our data obtained from human specimen from AVS or HOCM indicates major alterations in the expression of the mitochondrial calcium uniporter complex and associated proteins. Thus, in cardiac septal hypertrophies, besides modifications of cytosolic calcium handling, impaired mitochondrial uptake might be a key player in disease progression.